Management of contractual risks in a BIM-enabled project - Mustaffa, Nur Emma (2020)
Building Information Modelling (BIM) transforms the construction industry and one of the major hindrances highlighted is a lack of BIM standard form of contract. The consequence thereof, there is no standard clause which laid down the provision for variation order in a project which adopt BIM. This may lead to a contractual risk in running a BIM enabled project. In theory, it has been stated that no variation order is issued as visualization of the project is enhanced through models developed. Nonetheless, from practitioners' point of view, variation order still exists in BIM-based projects. Hence, this research tries to have a better understanding on the significance of variation order in the context of a BIM-enabled project and highlight the major requirements to be incorporated into variation order contractual provisions in the light of the establishment of a BIM standard form of contract. The research adopts a single case study approach based on a government administrative building and adopt interviews and documentary analysis as data collection methods. Two documents have been analyzed to understand the major requirements to be incorporated for BIM standard contract comprises of BIM Execution Plan adopted from BIM Guide 4 and BIM Protocol adopted from Construction Industry Council BIM Protocol 2018. The elements which have been identified to be relevant in variation order of BIM-based project were models for Site, Architectural, Plumbing and Water Supply, Drainage and Sewerage, and Specialist System. In terms of BIM Execution Plan there were five (5) sections and ten (10) sections respectively which have been suggested as major requirements to be incorporated in BIM standard contract of variation order contractual provisions incorporation. As for BIM Protocol, there were six (6) clauses which have been recommended for the variation order contractual provisions incorporation comprising of definition clause, obligations of the employer, obligations of project team member, electronic data exchange, use of information and liability in respect of proprietary material.